UPAYA MENGHADAP PEMBELAJARAN 4.0 DAN SOCIETY 5.0 PERSPEKTIF KI HADJAR DEWANTARA - Ina Wai, Florentina (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2025)
This study aims to explore Ki Hadjar Dewantara's thoughts on addressing the challenges of Learning 4.0 and Society 5.0, as well as their relevance in the context of modern education. The research method used is a literature study with a qualitative approach, analyzing ideas about the Fourth Industrial Revolution, Society 5.0, and Dewantara's concepts through primary and secondary sources. The findings indicate that the concept of education based on learning freedom and a balance between technology and humanistic values remains relevant in the digital era and technology-based society. This study is expected to enrich educational discourse by emphasizing the importance of building character and culture in technology-based learning processes, thereby producing learners who are not only digitally intelligent but also have a strong sense of nationalism and character.